WEATHER RADAR SYSTEMS TO IMPROVE LANDING SAFETY - Z.Z. Shamsiev; SH.F. Bahromov (Journal of new century innovations, 2023)
Abstract; The use of weather radar systems to enhance landing safety involves the application of advanced radar technology to provide critical weather information to pilots during the approach and landing phases of a flight. These systems utilize radar waves to detect and track precipitation, turbulence, and other meteorological phenomena in the vicinity of an airport. By offering real-time data on weather conditions, including factors like rain, snow, hail, and wind patterns, weather radar systems empower pilots and air traffic controllers to make more informed decisions regarding the timing and execution of landings. This information enables them to adjust flight paths, altitudes, and speeds to navigate safely through adverse weather conditions, thereby reducing the risk of accidents or incidents related to poor visibility or severe weather. Implementing weather radar systems in aviation contributes significantly to overall flight safety, allowing for more precise and reliable landings, even in challenging weather scenarios. This technology represents a crucial component of modern aviation, enhancing the ability to conduct safe and efficient operations in diverse weather environments.